1903 Okla. Rev. Stat. Ann. 643 ch. 25, art. 45, § 584 - (:unkn) unknown (My University, 1903)
Prohibited the carrying of any pistol, revolver, Bowie knife, dirk, dagger, slungshot, sword cane, spear, metal knuckles, or other kind of offensive or defensive weapon
Keywords: CARRY